2014
DOI: 10.1080/87565641.2013.870178
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Cognitive Outcomes in Children Following Perinatal Stroke

Abstract: Perinatal stroke is a significant cause of congenital neurological disability. Although motor deficits and epilepsy are relatively easy to identify, developmental and behavioral co-morbidities are more complex and challenging to define. We provide an overview of perinatal stroke syndromes and theories relating injury in the developing brain to long-term outcomes. We present a comprehensive overview of the effects on intelligence and other specific cognitive domains, as well as investigations relating clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 131 publications
3
32
0
3
Order By: Relevance
“…The barriers to the study of neuropsychological outcomes include the complexity of the timing of the appearance of specific deficits, the use of variable outcome measures, and studies with modest mixed samples that only rarely use a prospective longitudinal design. 4,30 We chose KeABCeII instead of the Wechsler Intelligence Scale for Children (WISC) because it allows a more valid assessment of children with suspected language impairment (with the possibility to interpret results by excluding verbal ability). 41 KeABCeII index scores have been found to correlate strongly with WISCeIV, 34,41 which makes the results of our study easily comparable to other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The barriers to the study of neuropsychological outcomes include the complexity of the timing of the appearance of specific deficits, the use of variable outcome measures, and studies with modest mixed samples that only rarely use a prospective longitudinal design. 4,30 We chose KeABCeII instead of the Wechsler Intelligence Scale for Children (WISC) because it allows a more valid assessment of children with suspected language impairment (with the possibility to interpret results by excluding verbal ability). 41 KeABCeII index scores have been found to correlate strongly with WISCeIV, 34,41 which makes the results of our study easily comparable to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes by pediatric stroke outcome measure (PSOM). Scoring criteria according to PSOM: Normal ¼ score 0 in all five subscales; Mild deficit ¼ score 0.5 in one subscale only; Moderate deficit ¼ score 0.5 in more than one subscale, or score 1 in one subscale, or score 1 in one subscale and 0.5 in another subscale; Severe deficit ¼ score 0.5 in all five subscales, or score 1 in one subscale plus 0.5 in two subscales, or score 1 or 2 in at least two subscales 30. …”
mentioning
confidence: 99%
“…2 Other studies have shown stability in cognitive scores, suggesting that the developing brain can buffer the effect of an early focal insult. 3 In most studies, the determinants of outcome have been primarily focused on presumably deleterious factors (lesion size or diagnosis of epilepsy, or a disorder of motor function like cerebral palsy [CP]), 1,4,5 but potentially protective factors have not been addressed. In addition, several studies have included various perinatal stroke syndromes where the timing, localization, and type of insults are diverse.…”
mentioning
confidence: 99%
“…This notion corroborates with a prior investigation that has suggested that children with HCP have deficits in cognitive processing. 52 This may indicate that the brain insults seen in children with HCP are not limited to sensorimotor areas only, but rather they have a cascading effect on the other cortical areas.…”
Section: Discussionmentioning
confidence: 99%